Myanmar: Unlocking the Potential. A Strategy for High, Sustained, and Inclusive Growth - Ronald Findlay; Cyn-Young Park; Jean-Pierre A. Verbiest (Asian Development Bank (ADB), 2015)
Recognizing the need to formulate policy strategies for the changes it faces, Myanmar started a multifaceted reform process in 2011. But speeding up development requires a multipronged but more coherent strategy targeted at strong and resilient growth, employment generation and, ultimately, rapid reduction of poverty. The government needs to carefully prioritize and sequence reforms, and identify and address the constraints to allow acceleration of economic growth by expanding the large domestic market and developing a vibrant manufacturing export sector that can generate substantial employment. This paper briefly reviews Myanmar's history and its legacy, examines the economy and some of the main policy reforms undertaken since 2011, assesses development potential, and outlines medium- and long-term growth strategy based on the country's specific context and international best experiences and practices.
hdl:11540/5056
Keywords: E02; E61; O14; O25; 330; economic diversification; macroeconomic stability; Myanmar; natural resource-based sectors; regionally balanced development; social inclusion